A luminescent and colorimetric probe based on the functionalization of gold nanoparticles by ruthenium(ii) complexes for heparin detection. Issue 19 (5th September 2017) - Li, Jing; Cheng, Meng; Li, Mei-Jin
Abstract : A colorimetric and luminescent bifunctional Ru(ii ) complex-modified gold nanoprobe for the sensing of heparin in Tris-HCl buffer (pH 7.4) and 1% fetal bovine serum (FBS) was developed. Abstract : A sensitive assay was demonstrated for the colorimetric and luminescent detection of heparin. Positively charged [Ru(phen)2 np] 2+ (np: naphtho[2, 3- f ][1, 10]phenanthroline) can interact with negatively charged AuNPs through electrostatic interaction, leading to the luminescence quenching of [Ru(phen)2 np] 2+ via energy transfer as well as the aggregation of AuNPs together with a color change in solution from red to blue. Upon the addition of negatively charged heparin to gold nanoparticles functionalized by ruthenium(ii ) complexes, the emission of [Ru(phen)2 np] 2+ recovered due to the competitive adsorption of [Ru(phen)2 np] 2+ to heparin and AuNPs. A linear calibration curve was obtained in the 0.4 μM to 100 μM range and 0.1 μM to 6 μM with a low detection limit of 0.22 μM and 0.024 μM based on 3 σ / s for heparin quantification in buffer solution and in 1% fetal bovine serum (FBS), respectively. Interestingly, the naked eye alone can judge the presence of 0.02 μM heparin without the aid of any advanced instruments by color change. Thus a convenient and visual method to detect heparin was established.